Methods For Analyzing Intergovernmental Fiscal Relations And Service Delivery In Imo State, Nigeria (2019–2024) - Abalaka, J.N; Ajiteru,S.A.R; Sulaiman T.H (International Journal of Social Welfare and Family Law, 2025)
Intergovernmental relations and local government performance in Nigeria's Imo State were the subjects of this study. Secondary data was gathered by reviewing textbooks, journals, magazines, online resources, and published and unpublished materials. Primary data was gathered by administering questionnaires to 270 respondents, who were selected from a sample population of 30 employees from each of the nine (9) local governments, three of which were chosen from each senatorial zone. According to the report, intergovernmental connections make sure that the various governmental levels use human and material resources effectively and efficiently. In a true federalism, it fosters the development of cooperation rather than rivalry. However, local governments lack sufficient funds, particularly from the state government. The effectiveness of local government is impacted by the usage of Transition Committees, Caretaker Committees, and even Sole Administrators. The researcher suggested that in order to address the irregularities, local governments should have elected governing bodies, practice true federalism, apply the rule of law principle, have their constitutionally specified areas of jurisdiction, and grant local governments autonomy. All of the aforementioned will guarantee that Imo State's local governments operate effectively